The effect of educational leadership on organizational variables: A meta–analysis study in the sample of Turkey - Çoğaltay, N.; Karadağ, E. (Edam, 2016)
The purpose of this study is to test the effect of educational leadership on some organizational variables using meta–analysis method. In this context, the results of independent researches were merged together and the hypotheses created within the scope of the study were tested. In order to determine the researches to be included in the study, first of all, a literature review was made in YOK, ULAKBIM, and Google Scholar databases. The findings of the researches, which have been conducted between the years 2000–2013, were included in the analysis; July 2013 has been set as the latest date. Using the developed scanning strategy, a total of 77 researches were reached and appropriate correlational data from these researches were included in the meta–analysis. The distribution of the researches according to topics is as follows: educational leadership and job satisfaction 14, organizational justice 9, organizational commitment 24, organizational trust 5, organizational citizenship 7, performance 5, organizational culture 4 and organizational climate 9. All meta–analysis are based on random effects model. The findings showed that educational leadership has large positive effects on job satisfaction [r= .56], organizational justice [r= .75], organizational commitment [r= .43], organizational trust [r= .73], organizational culture [r= .56] and organizational climate [r= .50], whereas it has medium positive effects on organizational citizenship [r= .35] and performance [r= .36]. © 2016 EDAM.
Keywords: Educational leadership; Leadership; Meta–analysis; Organizational variables